The prevalence of nutritional status and obesity in adolescents in Babylon Province, Iraq - Nihad Abdallah Selman; Ashraf M. A. Hussain; Nassar Abdalaema Abdalhadi Mera (Medical Journal of Babylon)
Abstract Background: Obesity is a chronic disease characterized by excessive fat accumulation that can lead to different complications. Objectives: However, identifying the prevalence of nutritional status and obesity in adolescents in Babylon governorate and searching for the relationship with different factors constitute the main objectives of this study. Materials and Methods: This study was cross-sectional study curried on 500 high school students aged between 16 and 19 years. Among them, half of them were female students. Study period was between February and June 2022; weight and height were measured to each participant to calculate body mass index (BMI) and they were requested to fill a questionnaire to identify any risk factor relation-ship. Results: Out of all, 14.2% were underweight, 55.4% were normal weight, 20.4% were overweight and 10% obese adolescents. There was a significant relationship between BMI from one hand and male gender, living in rural areas, high family income and soft drink (beverage consumption per week) on the other hand. Conclusion: The prevalence of overweight and obesity was around than one third (20.4% + 10% = 30.4% collectively, whereas 14.2% were underweight out of all participants in this study).